Didactic Conditions for the Development of Epistemological Motivation of Students in Teacher Education - Khudoikulova Dilrabo Shodmonovna (Scientific Trends, 2025)
This article notes that the development of gnoseological motivation of students in pedagogical education is an important part of the educational process, the use of innovative educational technologies in the educational process can also serve the personal development of students, a useful frame for society as a future specialist, responsible personnel are important for the sustainable development of any country.
Keywords: Motive, education, student,, process, profession, innovation, activity, quality, result.